2019
DOI: 10.1002/jctb.5988
|View full text |Cite
|
Sign up to set email alerts
|

Separation of a ternary mixture with multiple azeotropes via pressure‐swing distillation

Abstract: BACKGROUND The ternary mixture of tetrahydrofuran (THF), ethanol and water contains multiple azeotropes with the sensitivity to pressure variation. The pressure‐swing distillation (PSD) is a promising method to achieve the system's separation objective since it avoids many potential problems caused by adding a third component. RESULT A variety of separation sequences were synthesized on the ternary diagram, including the sequences of WLEMTH, WLTH EM, THEMWL, THWLEM, EMTHWL and EMWLTH. The optimal design parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The improved energy saving technologies, such as heat integration, 16,17 thermal coupling, 18,19 heat pump, 5,20−24 sidestream, 25 and intermediate reboiler 26 mixture by PSD with various energy-efficient technologies. Wang et al 17 studied ternary mixture separation by PSD with partial heat integration configuration. The results showed that heat integration can well improve the energy efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The improved energy saving technologies, such as heat integration, 16,17 thermal coupling, 18,19 heat pump, 5,20−24 sidestream, 25 and intermediate reboiler 26 mixture by PSD with various energy-efficient technologies. Wang et al 17 studied ternary mixture separation by PSD with partial heat integration configuration. The results showed that heat integration can well improve the energy efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The improved energy saving technologies, such as heat integration, , thermal coupling, , heat pump, , side-stream, and intermediate reboiler are used to achieve reduction in energy consumption in the distillation processes. Many researchers have investigated the separation of ternary mixture by PSD with various energy-efficient technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, special distillations such as extractive distillation (ED), heterogeneous azeotropic distillation (HAD), pressure‐swing distillation (PSD) and reactive distillation (RD) are adopted to separate such azeotropes. Arifin et al .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, special distillations such as extractive distillation (ED), 5-8 heterogeneous azeotropic distillation (HAD), [9][10][11][12][13] pressure-swing distillation (PSD) [14][15][16][17] and reactive distillation (RD) [18][19][20][21] are adopted to separate such azeotropes. Arifin et al 22 compared HAD and ED by total annual cost (TAC) to separate the azeotrope IPA + water, and results indicated that ED is more economic than HAD.…”
Section: Introductionmentioning
confidence: 99%